Comparative effects of dietary copper, zinc, essential oils, and chlortetracycline on nursery pig growth performance - Julie Ann Feldpausch; Jon A DeJong; Michael D Tokach; Steven S Dritz; Jason C Woodworth; Raghavendra G Amachawadi; Harvey M Scott; Jim L Nelssen; Robert D Goodband (Kansas Agricultural Experiment Station Research Reports, 2014)
A total of 350 weaned pigs (PIC 1050; initially 13.3 lb) were used in a 47-d study to compare the effects of feeding antibiotic alternatives (copper, zinc, and essential oils), alone or in combination, on nursery pig performance. Pigs were allotted to pens at weaning (d 0) and fed a common starter diet with no antimicrobial for 5 d before the start of the experiment. On d 5, pens of 5 pigs were allotted to 1 of 10 dietary treatments in a randomized complete block design with 7 replications per treatment. Dietary treatments were arranged in a 2 × 2 × 2 + 2 factorial with main effects of added copper sulfate (CuSO4; 0 vs. 125 ppm Cu), added zinc oxide (ZnO; none vs. 3,000 ppm Zn from d 5 to 12 and 2,000 ppm Zn from d 12 to 33), and Regano EX (0 vs. 45 g/ton essential oils blend; Ralco Animal Nutrition, Marshall, MN). The 2 additional treatments were growth-promoting and therapeutic levels of chlortetracycline (CTC at 50 or 400 g/ton). Pigs were fed experimental diets from d 5 to 33 followed by a common corn-soybean meal—based diet without any antimicrobial, essential oils, or pharmacological levels of Cu or Zn from d 33 to 47. To comply with FDA guidelines, CTC was removed on d 19 from the diet of pigs fed 400 g/ton CTC, then added again from d 20 to 33. All diets contained 16.5 ppm Cu and 165 ppm of Zn from the trace mineral premix. Essential oils had no effect on daily gain, but feeding CTC or pharmacological levels of Cu or Zn improved the growth rate of nursery pigs. Carryover effects from any of these dietary treatments on subsequent nursery growth performance were minimal. Although there were no improvements in feed efficiency due to Cu or Zn, the inclusion of an essential oils blend worsened feed and caloric efficiencies.; Swine Day, Manhattan, KS, November 20, 2014
Keywords: Swine Day; 2014; Kansas Agricultural Experiment Station contribution; no. 15-155-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1110; Chlortetracycline; Nursery pig; Antibiotic; Essential oil; Copper; Zinc